2017
DOI: 10.1590/1806-9282.63.02.173
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and autophagy: What is the relationship?

Abstract: Autophagy is a survival pathway wherein non-functional proteins and organelles are degraded in lysosomes for recycling and energy production. Therefore, autophagy is fundamental for the maintenance of cell viability, acting as a quality control process that prevents the accumulation of unnecessary structures and oxidative stress. Increasing evidence has shown that autophagy dysfunction is related to several pathologies including neurodegenerative diseases and cancer. Moreover, recent studies have shown that au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 92 publications
1
40
0
2
Order By: Relevance
“…Osteoblasts and osteocytes produce OPG (osteoprotegerin), a decoy receptor for RANKL, which binds to the cytokine and prevents its interaction with RANK, interrupting osteoclastogenesis [ 24 ].…”
Section: Bone Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoblasts and osteocytes produce OPG (osteoprotegerin), a decoy receptor for RANKL, which binds to the cytokine and prevents its interaction with RANK, interrupting osteoclastogenesis [ 24 ].…”
Section: Bone Remodelingmentioning
confidence: 99%
“…This phase allows the acidification and degradation of the delivered macromolecules into amino acids, lipids, nucleotides, and energy for further use by the cell [ 46 ]. Several proteins are involved like dynein, which regulates vesicular transport, Rab7, Beclin-1, SNAREs (soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptors), and many others that facilitate autophagosome maturation [ 24 , 25 ]. Some proteins such as p62, NBR1 (neighbor of BRCA1 gene), and ALFY (autophagy-linked FYVE protein) are located at the autophagosome surface and sequester the degradation targets [ 25 ].…”
Section: Autophagy and Bone Remodelingmentioning
confidence: 99%
“…In recent years, studies have shown that autophagy plays important roles for the maintenance of bone homeostasis, and its dysregulation has been related to bone loss and osteoporosis [18], [14][15][16][17]. It has been demonstrated that suppression of ATG7 (autophagy related 7), an essential gene for autophagy, in mice osteocytes promotes a marked increase in oxidative stress and bone loss [18].…”
Section: Introductionmentioning
confidence: 99%
“…These dysfunctional mitochondria accumulate in the cells due to defective clearance as a result of downregulated autophagy, so they continue to produce higher levels of superoxide anion that leak from them and attack other cellular components eventually leading to irreversible cellular damage and death . In addition, mitochondrial superoxide produced by SOD2 loss promotes the upregulation of the RANKL expression associated with a higher rate of bone resorption in mice .…”
Section: Discussionmentioning
confidence: 99%